Hybrid electrospun porous fibers of poly(lactic acid) and nano ZIF‐8@C600 as effective degradable oil sorbents. Issue 3 (27th November 2019) - Wang, Yating; Li, Xu; Dai, Xiu; Zhan, Yixing; Ding, Xiaoqing; Wang, Ming; Wang, Xinglong
Abstract: BACKGROUND: With the rapid industrial and urbanization development, a large amount of oily wastewater is generated from various sources. It is mutagenic and carcinogenic to human health and seriously affects the ecosystem. In this study PLA/ZIF‐8@C600 nanofibers were prepared for oil adsorption. RESULTS: Hybrid nanoparticles (ZIF‐8@C600) of carbon black C600 and zeolitic imidazolate framework‐8 (ZIF‐8) with high specific surface area and porous structure were prepared by co‐deposition and characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FITR) spectroscopy, X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), Raman spectroscopy and contact angle measurement. Biodegradable composite nanofiber membranes of poly(lactic acid) (PLA) and ZIF‐8@C600 were manufactured by electrospinning. The SEM and contact angle results showed that the addition of ZIF‐8@C600 could adjust the diameter, porosity, pore size and hydrophobicity of the composite electrospun nanofibers. The PLA/ZIF‐8@C600 porous membranes had good oil sorption properties in oil–water mixture and emulsion. The oil adsorption capacity of the sample with 1 wt% ZIF‐8@C600 was improved by ∼72.59% compared with that of pure PLA (13.5 g g −1 ), which demonstrated that the PLA/ZIF‐8@C600 fibers were good candidates as oil sorbents. The adsorption kinetics of the membranes on paraffin liquid was in accordance with pseudo‐second‐order kinetics. CONCLUSION: The addition of hybrid ZIF‐8@C600 improved the hydrophobic properties and oil adsorption capacity of PLA/ZIF‐8@C600 porous membranes. Because PLA is an environmentally friendly polymer, composite membranes based on it can avoid secondary pollution. Overall, these findings have good prospects for future treatment of oily wastewater. © 2019 Society of Chemical Industry